Discretisation techniques for large deformation computational contact elastodynamics - Franke, Marlon (Schriftenreihe des Instituts für Mechanik, Karlsruher Institut für Technologie, 2014)
The present thesis deals with large deformation contact problems of flexible bodies in the field of nonlinear elastodynamics. Special emphasis will be placed on a consistent spatial and temporal discretization. For the spatial discretization of the underlying bodies, the finite element method will be used. For the contact boundaries the collocation type node-to-surface method as well as the variationally consistent Mortar method will be applied.